Distinct properties of Ca2+ efflux from brain, heart and liver mitochondria: The effects of Na+, Li+ and the mitochondrial Na+/Ca2+ exchange inhibitor CGP37157. (June 2021) - Rysted, Jacob E.; Lin, Zhihong; Walters, Grant C.; Rauckhorst, Adam J.; Noterman, Maria; Liu, Guanghao; Taylor, Eric B.; Strack, Stefan; Usachev, Yuriy M.
Graphical abstract: Highlights: Mitochondrial Na + /Ca 2+ exchanger is active in brain and heart, but not in liver. NCLX is expressed in brain, heart and liver. Li + is significantly less effective than Na + in driving mitochondrial Ca 2+ efflux. Abstract: Mitochondrial Ca 2+ transport is essential for regulating cell bioenergetics, Ca 2+ signaling and cell death. Mitochondria accumulate Ca 2+ via the mitochondrial Ca 2+ uniporter (MCU), whereas Ca 2+ is extruded by the mitochondrial Na + /Ca 2+ (mtNCX) and H + /Ca 2+ exchangers. The balance between these processes is essential for preventing toxic mitochondrial Ca 2+ overload. Recent work demonstrated that MCU activity varies significantly among tissues, likely reflecting tissue-specific Ca 2+ signaling and energy needs. It is less clear whether this diversity in MCU activity is matched by tissue-specific diversity in mitochondrial Ca 2+ extrusion. Here we compared properties of mitochondrial Ca 2+ extrusion in three tissues with prominent mitochondria function: brain, heart and liver. At the transcript level, expression of the Na + /Ca 2+ /Li + exchanger (NCLX), which has been proposed to mediate mtNCX transport, was significantly greater in liver than in brain or heart. At the functional level, Na + robustly activated Ca 2+ efflux from brain and heart mitochondria, but not from liver mitochondria. The mtNCX inhibitor CGP37157 blocked Ca 2+ efflux from brain and heart mitochondria but had no effect in liver mitochondria. Replacement of Na + with Li + to test the involvement of NCLX, resulted in a slowing of mitochondrial Ca 2+ efflux by ∼70 %. Collectively, our findings suggest that mtNCX is responsible for Ca 2+ extrusion from the mitochondria of the brain and heart, but plays only a small, if any, role in mitochondria of the liver. They also reveal that Li + is significantly less effective than Na + in driving mitochondrial Ca 2+ efflux.